An Evaluation of the Implementation of Tax Scheme Reporting Procedures - Hyży, Maciej Leszek (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The purpose of the article is to evaluate the tax scheme reporting procedures selected companies use. Research Design & Methods: Legal acts, the subject literature and a case study were analysed. Findings: The study shows that the implementation of tax scheme reporting procedures offers both advantages and disadvantages. The main advantage is that the procedures have enabled more effective tax risk management. The main drawback is that in all of the entities surveyed, the management board and heads of finance and accounting departments had problems understanding the terms used in the tax code related to tax patterns. Implications / Recommendations: The research shows that the effective implementation of tax scheme reporting procedures enables more effective tax risk management. Further research is needed, with a view to showing that implementing tax reporting procedures mitigates the risk of making a mistake when reporting tax schemes. Contribution: The original contribution of the article is its presentation and characterisation of the elements of the tax patterns reporting procedure.